Amplified Detection of the Aptamer—Vanillin Complex with the Use of Bsm DNA Polymerase - Mariia Andrianova; Natalia Komarova; Sergey Glukhov; Alexander Kuznetsov (Proceedings, 2017)
The decreased sensitivity for electrochemical detection of low-molecular-weight targets with the use of aptamers is a great problem of scientific importance. [...]